Prospective measurement of quality of life in myotonic dystrophy type 1. (28th June 2017) - Peric, S.; Heatwole, C.; Durovic, E.; Kacar, A.; Nikolic, A.; Basta, I.; Marjanovic, A.; Stevic, Z.; Lavrnic, D.; Rakocevic Stojanovic, V.
Abstract : Introduction: Generic patient reported outcome measures have had varied success in tracking QoL in myotonic dystrophy type 1 (DM1). Aim: To analyze changes of Individualized Neuromuscular Quality of Life questionnaire (INQoL) scores in clinic patients with DM1 over a 6‐year period. Method: Patients completed the INQoL at baseline and after a 6‐year period through their attendance in a neurology outpatient clinic. Severity of muscular involvement in DM1 was analyzed using the Muscular Impairment Rating Scale (MIRS). Results: Ninety‐nine DM1 patients completed a baseline visit. Sixty‐seven of these patients were retested at an interval time. The overall INQoL score improved in our sample of patients ( P <.05) as did the following subscales: myotonia ( P <.05), pain ( P <.05), activities ( P <.01), social relationships ( P <.01), and body image ( P <.05). No changes were observed for the independence and emotions scales. There were no differences in mean change of INQoL scores between patients with worsened MIRS and those with no change in MIRS scale after follow‐up ( P >.05). Conclusion: Individualized Neuromuscular Quality of Life questionnaire scores improved in our cohort of DM1 patients during a 6‐year period. INQoL score did not correlate with progression of muscle weakness. This must be better understood before the selection of the instrument for use in trials to measure therapeutic benefit in DM1 patients.